The Stage of Human Creation in the Qur'an al-Karim and the Sunnah of the Prophet - Ismail Abdul Ghani al-Jalal (Demak Universal Journal of Islam and Sharia, 2023)
This research aims to correct misunderstandings and invalidate suspicions and theories relating to the creation of man and his origins, and to demonstrate a complete correspondence between what is stated in the Qur'an and the Sunnah of the Prophet and what is confirmed by scientific facts. This approach uses an inductive model where we will follow the Qur'anic approach in presenting this important issue in human life. The results of the study concluded that: first, the creation of man went through three main stages: starting creation from dust: (The creation of Adam), which went through various forms, as revealed by the Qur'an.  the creation of Eve from Adam's rib, and the creation of Adam's descendants. In the second stage, humans were created from sperm from Adam's offspring and did not evolve from other creations. Third stage: Invalidity of Darwin's theory with forensic evidence and scientific facts. تهدف الدراسة إلى تصحيح التصورات الخاطئة وإبطال الشبهات والنظريات المتعلقة بخلق الإنسان وأصله، وبيان التطابق التام بين ما جاء في القرآن الكريم وصحيح السنة النبوية المطهرة وبين ما أكدته الحقائق العلمية. منهج استقرائي حيث سنسير وفق المنهج القرآني في عرضه لهذه القضية المهمة في حياة الإنسان وذلك أجدى لبيان التطابق بينه وبين ما جاءت به أبحاث الإعجاز العلمي من خلال هذا البحث الموجز نخلص إلى النتائج التالية: أولاً: أن خلق الإنسان مرّ بثلاث مراحل رئيسية، هي: مرحلة بدء الخلق من تراب: (خلق آدم عليه السلام)؛ حيث مرّت بصور مختلفة؛ عبر عنها القرآن الكريم بعدة تعبيرات بحسب تغير صفة هذه المادة وأحوالها, مرحلة خلق حواء من ضلع آدم, مرحلة خلق ذرية آدم في صلبه أثناء خلقه